A Pyrazolo[3,4-d]pyrimidine Compound Reduces Cell Viability and Induces Apoptosis in Different Hematological Malignancies - Laurenzana, Ilaria; Caivano, Antonella; La Rocca, Francesco; Trino, Stefania; De Luca, Luciana; D’Alessio, Francesca; Schenone, Silvia; Falco, Geppino; Botta, Maurizio; Del Vecchio, Luigi; Musto, Pellegrino (Frontiers in Pharmacology, 2016)
Molecular targeted therapies are based upon drugs acting on tumors by interfering with specific targets involved in growth and spread of cancer. Many targeted therapies were approved by Food and Drug Administration as standard treatment, others were introduced into preclinical or clinical studies on hematological malignancies (HMs). The development of drug-resistance in some HMs and the lack of effective treatments in other ones emphasized the need for searching new molecular targets and therapeutic agents. The aim of this study was to evaluate the effects of 4c pyrazolo[3,4-d]pyrimidine compound, a Src inhibitor, on lymphoid and myeloid neoplasms. Here, we demonstrated its ability to reduce cell viability, induce apoptosis and cell cycle arrest in lymphoid cell lines such as Jurkat, SKMM1, Derl-2/7, and myeloid cell lines, such as Jurl-MK1. Moreover, we reported a high expression of a Src kinase, Fyn, in these cell lines compared to healthy subjects. This study was a starting point to investigate 4c pyrazolo[3,4-d]pyrimidine compound as a drug for HMs and Src kinases as its potential molecular targets.